Effectiveness of etanercept in bleomycin-induced experimental scleroderma - Koca, S. S.; Isik, A.; Ozercan, I. H.; Ustundag, B.; Evren, B.; Metin, K. (Oxford Univ Press, 2008)
Objectives. To evaluate the effects of etanercept and thalidomide in the mouse model of bleomycin-induced scleroderma (BLM-IS). Methods. This study involved four groups (n=8 mice in each group). Dermal sclerosis was induced by repeated subcutaneous injections of BLM (10 mu g) for 4 weeks in BALB/c mice. Control group received only phosphate-buffered saline. The second group received only BLM; the third and fourth groups were also given an intraperitoneal injection of 100 mu g etanercept or 150 mg/kg thalidomide, respectively. Results. BLM increased serum TGF-beta(1), tissue hydroxyproline levels and expression of alpha-smooth muscle actin (alpha-SMA), and dermal fibrosis was histopathologically prominent. Although thalidomide had no significant effect, etanercept caused decreases in levels of serum TGF-beta(1), tissue hydroxyproline and number of alpha-SMA-positive cells. Conclusion. Inhibition of TNF-alpha with etanercept in BLM-IS was resulted in a significant reduction of the dermal sclerosis, collagen accumulation and the number of infiltrating myofibroblastic cells. TNF-alpha may play a key role in the progression of BLM-IS and TNF-alpha antagonists may be useful in the management of scleroderma.
Keywords: scleroderma; bleomycin; etanercept; animal model